An analysis of pre-and posttest scores of biology teachers in five RSTCs - Formacion, Minda B. Jamilosa 1946-
The aim of this study was to make use of residual gain scores and analysis of variance in comparing the performance of the teacher-participants of the five Regional Science Teaching Centers (RSTC) in the 2 tests given (i.e. Achievement Test in Biology and the Processes of Science Test) during the 1972 Science Summer Institute.